2002
DOI: 10.1007/s00122-001-0819-7
|View full text |Cite
|
Sign up to set email alerts
|

QTL clusters reflect character associations in wild and cultivated rice

Abstract: The genetic basis of character association related to differentiation found in the primary gene pool of rice was investigated based on the genomic distribution of quantitative trait loci (QTLs). Major evolutionary trends in cultivated rice of Asiatic origin ( Oryza sativa) and its wild progenitor ( O. rufipogon) are: (1) differentiation from wild to domesticated types (domestication), (2) ecotype differentiation between the perennial and annual types in wild races, and (3) the Indica versus Japonica type diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
1
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 258 publications
(170 citation statements)
references
References 41 publications
16
152
1
1
Order By: Relevance
“…Moreover, The two QTLs, qANL-5 and qANL-9, were also identified near regions where Xiong et al (1999) detected two of the seven QTLs for ANL using simple interval mapping based on a LOD score > 2.4. The results from this study, together with those reported by Xiong et al (1999) and Cai and Morishima (2002), suggest that the variation in anther length between cultivated rice and its wild relatives was controlled by a relatively large number of QTLs compared to pistil traits. Comparative mapping among different populations is needed to confirm this hypothesis, since different field conditions and thresholds were used to detect QTLs in these studies.…”
Section: Stamensupporting
confidence: 64%
See 4 more Smart Citations
“…Moreover, The two QTLs, qANL-5 and qANL-9, were also identified near regions where Xiong et al (1999) detected two of the seven QTLs for ANL using simple interval mapping based on a LOD score > 2.4. The results from this study, together with those reported by Xiong et al (1999) and Cai and Morishima (2002), suggest that the variation in anther length between cultivated rice and its wild relatives was controlled by a relatively large number of QTLs compared to pistil traits. Comparative mapping among different populations is needed to confirm this hypothesis, since different field conditions and thresholds were used to detect QTLs in these studies.…”
Section: Stamensupporting
confidence: 64%
“…All QTLs increased anther length at the wild rice allele. Three out of four QTLs were identified in the vicinity of QTL regions previously detected for ANL using simple interval mapping based on a LOD score > 3.0 (Cai and Morishima 2002). Moreover, The two QTLs, qANL-5 and qANL-9, were also identified near regions where Xiong et al (1999) detected two of the seven QTLs for ANL using simple interval mapping based on a LOD score > 2.4.…”
Section: Stamenmentioning
confidence: 98%
See 3 more Smart Citations